Influenza vaccine failure: failure to protect or failure to understand? - Gregory A. Poland (Taylor & Francis Group, 2018)
Introduction: I propose that influenza vaccine failure be defined as receipt of a properly stored and administered vaccine with the subsequent development of documented influenza. Several mechanisms of vaccine failure occur and can - sometimes in combination - lead to what is termed 'vaccine failure.' Influenza vaccine failure occurs for many reasons, many of which are not true failures of the vaccine (e.g. improper vaccine storage/handling). Areas covered: In this article, I discuss common causes of 'vaccine failure' that are appropriately or inappropriately attributed to vaccines. This includes host, pathogen, vaccine, and study design issues such as genetic restriction of immune response; failure to store, handle, and administer vaccine properly; issues of immunosuppression and immunosenescence; apparent but false vaccine failure; time-mediated failure; etc. Expert commentary: A proper framework and nosology for vaccine failure informs discussion about influenza vaccine efficacy and prevents misperceptions that in turn affect vaccine uptake. Influenza vaccine can only provide maximum protection to the extent that the circulating and vaccine strains closely match; the vaccine is stored, handled, and administered properly and within a time frame to result in development of protective levels of immunity; and it is administered to a host capable of immunologically responding with protective immune responses.